Tingkat Pengetahuan Pasien dan Rasionalitas Swamedikasi di Apotek Kecamatan Colomadu - Sulfiatus Sholiha; Amal Fadholah; Lija Oktya Artanti (Pharmasipha : Pharmaceutical Journal of Islamic Pharmacy, 2019)
Self-medication is a part of the community's efforts to deal with minor illnesses by using over-thecounter drugs, limited over-the-counter drugs, and mandatory drug medicines without consulting a doctor first. This study was conducted to analyze the level of knowledge and rationality of the use of self-medication. Respondents had the aged in the range of 18-60 years at five Colomadu district drug stores. The retrieval data were done by interviewing used a questionnaire that had tested for validity and reliability. The respondents 110 with consecutive sampling method from five drug stores in Colomadu District. Data were analyzed by Chi-square test using Statistical Product and Servicer Solution (SPSS) version 17. The results showed that the level of knowledge of patients 37.3% wasclassified as poor, 39.1% classified as moderate and 23.6% classified as good. The use of selfmedication was 17.3% irrational and 82.7% rational. Based on the results of the chi-square test, the level of knowledge and rationality of self-medication was not influenced by gender, age, last education, and occupational factors. Based on the results of the study it was found that the level of knowledge of patients classified as moderate with a percentage of 39.1%. The rationality of selfmedication classified as rational with a percentage of 82.7%.